Water Circulation and Marine Environment in the Antarctic Traced by Speciation of 129I and 127I - Shan Xing (Nature Portfolio, 2017)
Abstract Emissions of anthropogenic 129I from human nuclear activities are now detected in the surface water of the Antarctic seas. Surface seawater samples from the Drake Passage, Bellingshausen, Amundsen, and Ross Seas were analyzed for total 129I and 127I, as well as for iodide and iodate of these two isotopes. The variability of 127I and 129I concentrations and their species (127I−/127IO3 −, 129I−/129IO3 −) suggest limited environmental impact where ((1.15–3.15) × 106 atoms/L for 129I concentration and (0.61–1.98) × 10−11 for 129I/127I atomic ratios are the lowest ones compared to the other oceans. The iodine distribution patterns provide useful information on surface water transport and mixing that are vital for better understanding of the Southern Oceans effects on the global climate change. The results indicate multiple spatial interactions between the Antarctic Circumpolar Current (ACC) and Antarctic Peninsula Coastal Current (APCC). These interactions happen in restricted circulation pathways that may partly relate to glacial melting and icebergs transport. Biological activity during the warm season should be one of the key factors controlling the reduction of iodate in the coastal water in the Antarctic.